Impact of Environmental Factors on Clostridium perfringens Sporulation Isolated from Poultry Droppings-Contaminated Soils in the of Poultry Farms - Singh Rajawat, Abhishek; Kumari, Shailja (Journal of Neonatal Surgery, 2025)
The persistence and pathogenicity of Clostridium perfringens, a spore-forming anaerobic bacterium, in poultry farm environments pose significant risks to animal health and food safety. This study aimed to investigate the influence of environmental factors—such as humidity, pH, temperature, and oxygen availability—on the growth and sporulation of C. perfringens isolated from poultry droppings-contaminated soils in the Malwa region of Madhya Pradesh, India. A total of 63 soil samples were collected from poultry farms across Ratlam, Mandsaur, Ujjain, and Indore. Five isolates (7.94%) tested positive for C. perfringens through biochemical, morphological, and phenotypic characterization. Controlled laboratory experiments revealed that optimal growth occurred at 35°C and pH 7.0 under strictly anaerobic conditions, with significant enhancement of sporulation at high humidity levels (90% RH). Antibiotic susceptibility profiling showed highest sensitivity to Ciprofloxacin, Rifampin, and Chloramphenicol, while resistance was observed against Amoxicillin, Gentamicin, and Vancomycin. These findings highlight the environmental resilience of C. perfringens and emphasize the importance of environmental management and targeted antibiotic use in poultry farming.